Shear Bond Strength of Ah26 to Human Dentin Treated with Dimethyl Sulfoxide (Dmso) - Fotis Dimopoulos; Konstantinos Kodonas; Christos Gogos (MDPI AG, 2022)
The purpose of this study was to examine the bond strength of AH26 to human coronal dentin exposed to DMSO. A total of 70 dentin specimens were equally divided into two groups. Each dentin surface was pre-treated with 2 mL of 2.5% NaOCl, 3 mL of EDTA 17%, and distilled water. One group was finally rinsed with 50% DMSO. Following the AH26 application, the bond strength was tested by subjecting the samples to a shear load at a crosshead speed of 0.5 mm/min using universal testing equipment. The results according to paired samples t-test indicated that there was a statistically insignificant difference between the two groups. Therefore, DMSO had no effect on the bond strength of AH26 root sealer to dentin.